1991
DOI: 10.1139/z91-168
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in natural populations of the gray wolf, Canis lupus

Abstract: The genetic variability of gray wolves (Canis lupus) from northwestern Canada was assessed through starch-gel electrophoresis. Of 27 protein systems examined, 25, representing 37 presumptive loci, were consistently scorable; 7 proteins (5 were consistently scorable) exhibited polymorphism. The level of heterozygosity (3.0%) was medial relative to values reported for natural populations of Carnivora and high relative to values reported for natural populations of canids. An overall pattern of few deviations from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Allozymic variation of polymorphic loci were consistent with those reported for carnivores (O'Brien, 1980;Simonsen, 1982;Hartl et al, 1988;Evans et al, 1989;Mitton and Raphael, 1990;Kennedy et al, 1991;Randi et al, 1993). Despite a high level of allozymic polymorphism (24%), polecat populations exhibited a clear heterozygote deficiency.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Allozymic variation of polymorphic loci were consistent with those reported for carnivores (O'Brien, 1980;Simonsen, 1982;Hartl et al, 1988;Evans et al, 1989;Mitton and Raphael, 1990;Kennedy et al, 1991;Randi et al, 1993). Despite a high level of allozymic polymorphism (24%), polecat populations exhibited a clear heterozygote deficiency.…”
Section: Discussionsupporting
confidence: 87%
“…Far from being panmictic, numerous social species are however structured into small breeding units that are susceptible to amplify inbreeding. Thus, a family effect can affect the genetic structure of social species living either in packs, such as wolves (Kennedy et al, 1991;Randi et al, 1993;Forbes and Boyd, 1996), or in small colonies, such as badgers or mongooses (Evans et al, 1989;Keane et al, 1996;Vuuren and Robinson, 1997). Similarly, polygyny may increase inbreeding by reducing the effective number (Ne) of breeders.…”
Section: Introductionmentioning
confidence: 99%
“…In the Italian wolf, estimates of polymorphism and heterozygosity (P = 0.146, H e = 0.037) are intermediate as compared to the range of values reported for natural populations of wolf-like canids (Fisher et al 1976, Wayne et al 1991, Kennedy et al 1991, but are similar to recently published data on some gray wolf populations (Table 4). P-and //-values in the present study are higher than those obtained previously for the Italian wolf population , which is due to the identification of Ada as an additional highly variable locus.…”
Section: Discussionsupporting
confidence: 82%
“…Minnesota (33) p% ( Loci that we have found polymorphic in Italian wolves, were also polymorphic in other wolf populations (Kennedy et al, 1991;Wayne eta!., 1991), and in several dog breeds (Meera Khan eta!., 1973;Weiden et a!., 1974;Fisher et a!., 1976;Arnold & Bouw, 1985). Preliminary restriction fragment length polymorphism (RFLP) analysis showed that mtDNA was monomorphic in 14 Italian wolves collected by the Italian Institute for Wildlife Biology (INFS) during 1986(Wayne et a!., 1992.…”
Section: Discussionmentioning
confidence: 56%
“…Though Italian and Canadian wolves show similar values of heterozygosity and percentage of polymorphic loci (Table 4), the former are monomorphic at ME-I and PGM-1, where the latter are polymorphic, with variants at low frequencies (Kennedy et a!., 1991). It may be expected that a relatively large and uniformly distributed sample of wolves in Italy would increase the probability of detecting polymorphic loci, although this might be counteracted by both isolation and demographic fluctuations.…”
Section: Discussionmentioning
confidence: 97%